2020
DOI: 10.1017/s1047951120001018
|View full text |Cite
|
Sign up to set email alerts
|

Registry-based trials: a potential model for cost savings?

Abstract: Background/Aims:Registry-based trials have emerged as a potentially cost-saving study methodology. Early estimates of cost savings, however, conflated the benefits associated with registry utilisation and those associated with other aspects of pragmatic trial designs, which might not all be as broadly applicable. In this study, we sought to build a practical tool that investigators could use across disciplines to estimate the ranges of potential cost differences associated with implementing registry-based tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In this study, the STRESS Registry-Based and Pragmatic designs had much lower costs than the Explanatory design ($10,140,263 vs. $4,164,863 vs. $3,268,504, respectively). While this finding supports the position that it is the pragmatic design that accounts for a significant portion of the reduction in total costs previously reported for registry-based RCTs [ [13] , [14] , [15] ], it does not account for the further cost reduction associated with the Registry-Based versus Pragmatic design.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this study, the STRESS Registry-Based and Pragmatic designs had much lower costs than the Explanatory design ($10,140,263 vs. $4,164,863 vs. $3,268,504, respectively). While this finding supports the position that it is the pragmatic design that accounts for a significant portion of the reduction in total costs previously reported for registry-based RCTs [ [13] , [14] , [15] ], it does not account for the further cost reduction associated with the Registry-Based versus Pragmatic design.…”
Section: Discussionsupporting
confidence: 72%
“…Some studies indicate that registry-based RCTs can dramatically reduce clinical trial costs [ 13 , 14 ]. However, other studies note that these cost savings may have resulted from their incorporation of pragmatic trial design elements and not specifically their use of registries [ 15 ]. The Clinical Trials Transformation Initiative's (CTTI) Recommendations for Registry Trials concluded that embedding RCTs within registries may be associated with improvements in [ 1 ]: data collection [ 2 ], patient identification and recruitment [ 3 ], database lock time [ 4 ], time to critical decision-making, and [ 5 ] RCT costs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential advantages of registry‐based clinical trials to evaluate interventions compared with standard randomised controlled trials (RCTs) have been well documented 5‐9 . A major benefit is that registry‐based trials can represent broader population groups.…”
Section: Registry‐based Clinical Trials: Advantages and Limitationsmentioning
confidence: 99%
“…With an emphasis on collaboration, there have been dynamic changes in the structure of scientific activity [ 4 •], which includes the flexibility to provide funding to address urgent needs, overcoming the potentially elevated costs associated with extensive international collaboration. Registries are more cost effective than RCTs, and depending on study characteristics, can result in savings of up to USD 600,000 on data-associated costs alone [ 5 ].…”
Section: Introductionmentioning
confidence: 99%